Tourism information system using geographical information system - Ahmad Muzamir, Mazlan (2006)
In Penang,There are several places of attraction for tourist around the world to come here to have vacation. Unfortunately,Jabatan Pelancongan Pulau Pinang only uses the manual system for the tourist to explore and go to the certain places.For example,the tourist will refer to the magazines,books,pampWets and manual maps to search for certain places.Tourist also cannot record the information safely using the manual system.They also have problem in searching the places in Penang and have to ask other people to get detail information.This situation can make them difficult to find places and always loss the information about certain places.By using Tourism Information System Using GIS,tourist can search and get information about certain places easily.Tourist only needs to refer the map and click to the places that they want to get information. The map also can be enlarge in certain size and looks more interactive for clearer view.Hopefully,this system can solve the problems faced by the tourist and be a new method for promoting tourism in Penang.